Digital Culture - Undergraduate - Arditi, David; Miller, Jennifer (TRAILS: Teaching Resources and Innovations Library for Sociology, 2020)
Idealist thinking marked the development of the Internet and digital technologies, especially in the 1990s. Writers, both academic and popular, imagined a more democratic world where information would be unrestricted, communication would erase space, and technologies would free our time. In many ways, rhetoric about the Internet and other digital technologies parallel the uncritical hope many found in the technological inventions of the scientific revolution and philosophical edicts of the Enlightenment. In Dialectic of Enlightenment, Theodor Adorno and Max Horkheimer demonstrate that the exact developments in science and technology heralded by enlightenment thinkers as elevating freedom actually resulted in greater oppression of the masses. This course will look at the contradictions inherent in digital technologies and big data. Students will critically examine the rhetoric surrounding digital technologies. Ultimately, students will analyze questions about democracy, freedom, and equality.